La obra legislativa de Justiniano y la Cristianización del cosmos - González Fernández, Rafael (Antigüedad y Cristianismo, 1990)
The religious legislation of the Emperor Justinian was published during a period of ideological strictness. Nevertheless we find in his work not only a large quantity of traditional legislation with evident pagan precedents but also new laws which gather together the spirit and way of thinking of the new times. These laws will be the expression of all the thinking of this new period based on the dominating criterium provided by the Christian cosmology.